Technological professional education: a review on teachers’ continuing education - Keller, Raiara Valau (2020)
The present study seeks to analyze teacher’s education for acting in the Technological Professional Education (TPE), besides it discusses the importance of Continuing Education (CE) of Physical Education Teachers in this modality of teaching. For this, a historical analysis of the TPE was performed, the importance that the CE has and what it implies in the formative path. For the development of this study, a bibliographic research was used. Finally, it was clear the importance of building and / or enabling CE spaces for TPE teachers to instrumentalize to face the peculiarities of this teaching modality and, thus, be able to think about their pedagogical practice.